The combined use of Pochonia chlamydosporia and plant defence activators - a potential sustainable control strategy for Meloidogyne chitwoodi - VIEIRA DOS SANTOS, Maria Clara; CURTIS, Rosane; ABRANTES, Isabel (Phytopathologia Mediterranea, 2014)
Sustainable strategies are required for control of the root-knot nematode Meloidogyne chitwoodi to reduce dependence on toxic chemical pesticides. The efficacy of the nematophagous fungus Pochonia chlamydosporia in biocontrol could be enhanced by integration with control measures that reduce initial nematode infestations. The use of foliar sprays with plant defence activators can reduce the susceptibility of potato plants to M. chitwoodi. This study assessed effects of combined soil application of P. chlamydosporia with foliar sprays of benzothiadiazole (BTH) or cis-jasmone on infection of potatoes by M. chitwoodi. Solanum tuberosum, cv. Désirée plants were grown in soil mixed with 5000 chlamydospores g-1 of soil, sprayed twice with BTH or cis-jasmone and inoculated with 300 M. chitwoodi second-stage juveniles. Forty-five days after inoculation, nematode reproduction, numbers of colony-forming units of the fungus g-1 of soil and g-1 of root, and egg parasitism were assessed by standard techniques. Foliar sprays of BTH or cis-jasmone combined with the fungus reduced nematode reproduction (P<0.05, LSD). The presence of the fungus slightly increased the efficacy of cis-jasmone, as the number of eggs per egg mass was less in plants treated both with cis-jasmone and the fungus than in the plants treated only with the defence activator. The proportion of parasitized eggs was greater in the cis-jasmone treatment where rhizosphere colonisation was less, suggesting that P. chlamydosporia became a poorer rhizosphere coloniser but a more efficient nematode parasite. The addition of P. chlamydosporia to soil in combination with application of inducers of plant defence could be an alternative control strategy to be used against M. chitwoodi in potato.